Chemical attributes of an Oxisol after successive applications of organic compound with pig slurry - Lourenzi, Cledimar Rogério; Scherer, Eloi Erhard; Ceretta, Carlos Alberto; Tiecher, Tadeu Luis; Cancian, Adriana; Ferreira, Paulo Ademar Avelar; Brunetto, Gustavo (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine changes in the chemical attributes of an Oxisol after successive applications of organic compounds with pig slurry and wood shavings, under a no‑tillage system. The experiment was conducted in the municipality of Chapecó, in the state of Santa Catarina, Brazil, in an Oxisol, from September 2005 to August 2011. The doses of 0, 2, 4, 8, and 16 Mg ha-1 compound with pig slurry and shavings were applied annually, as well as a treatment with mineral fertilizer (NPK). After six applications, soil was collected at the 0–4, 4–8, 8–12, 12–16, 16–20, 20–40, and 40–60‑cm layers and the chemical attributes were evaluated. The highest doses of the organic compound increased soil pH and reduced potential acidity. The applications of the organic compound derived from swine manure and wood shavings promoted changes in the chemical attributes of the evaluated Oxisol, especially in the upper soil layers, with greater emphasis on increased soil pH and P, K, Cu, and Zn contents. The use of 4 Mg ha-1 of the compound maintains the soil chemical attributes similar to those of the NPK treatment, which followed official recommendation for the states of Rio Grande do Sul and Santa Catarina, besides keeping the P content in the surface layers within the environmental critical limit for soils with high clay content.